Insecticidal activity of ethanolic extracts from seed and leaf of bakain (Melia azedarach) and its effect on oviposition and egg hatching of Pieris brassicae in mid hills of Uttarakhand - MAURYA, R P; KUSHWAHA, M L; YADAV, L B (The Indian Journal of Agricultural Sciences, 2026)
The effect of ethanolic extracts from the leaves and seeds of bakain (Melia azedarach L.) on insecticidal activity, oviposition deterrent and egg hatchability of Pieris brassicae were studied under laboratory conditions at V C S G College of Horticulture, Bharsar, Pauri Garhwal, Uttarakhand during 2010. Six concentrations, viz. 1, 2, 4, 6, 8 and 10% of ethanolic extracts from both leaves and seeds of bakain were prepared and compare with 0.5% nimbecidine and control (water). As the doses increased, mortality of 2nd instar larvae of P. brassicae was also increased at each concentration from 1 to 10% after 24 hr of treatment. Highest mean mortality (66.67 %) was recorded at 10% concentration of bakain seeds followed by 10% bakain leaves (56.67% mean mortality). LC50 values from seeds and leaves extracts were 8.30% and 9.59%, respectively against 2nd instar larvae of P. brassicae. This LC50 indicates the toxicity of M. azedarach to the insects at higher concentrations. Egg laying by female adults at treated surfaces (muslin) proportionately decreased as the concentration of extracts increased. Egg laying at 10% bakain seed treated surface (8.00 eggs), 8% (14.67 eggs) and 6%(19.67 eggs) and bakain leaves at 10% (11.33 eggs) and 8% (17.33 eggs) were significantly better than nimbecidine 0.05% (23.00 eggs) and control (65.33 eggs). All the substrates treated with different concentrations had significantly adverse effect on the egg hatching as compared with the control. Distinct adverse effects on hatching were reported when the eggs were directly treated in different concentrations of extracts. Maximum 100% egg hatching reduction was recorded at 10% concentrations from both leaves and seed extracts. Finally it was concluded that M. azedarach was toxic to P. brasicae larvae with high LC50 values and it had oviposition deterrent effect and adverse effect on egg hatchability.